A joint industry‐sponsored data monitoring committee model for observational, retrospective drug safety studies in the real‐world setting. Issue 1 (24th November 2020) - Major‐Pedersen, Atheline; McCullen, Mary Kate; Sabol, Mary Elizabeth; Adetunji, Omolara; Massaro, Joseph; Neugut, Alfred I.; Sosa, Julie Ann; Hollenberg, Anthony N.
Abstract: Purpose: To share better practice in establishing data monitoring committees (DMCs) for observational, retrospective safety studies with joint‐industry sponsorship. Methods: A DMC model was created to monitor data from an observational, retrospective, post‐authorization safety study investigating risk of medullary thyroid cancer in patients treated with long‐acting glucagon‐like peptide‐1 receptor agonists (LA GLP‐1RAs) (NCT01511393). Sponsors reviewed regulatory guidelines, best practice and sponsors' standard operation procedures on DMCs. Discussions were held within the four‐member consortium, assessing applicability to observational, retrospective, real‐world studies. A DMC charter was drafted based on a sponsor‐proposed, adapted DMC model. Thereafter, a kick‐off meeting between sponsors and DMC members was held to receive DMC input and finalize the charter. Results: Due to this study's observational, retrospective nature, assuring participant safety – central for traditional explanatory clinical trial models – was not applicable to our DMC model. The overall strategy and key indication for our real‐world model included preserving study integrity and credibility. Therefore, DMC member independence and their contribution of expert knowledge were essential. To ensure between‐sponsor data confidentiality, all study committees/corporations and sponsors, besides the DMC, received blinded data only (adapted to refer to data blinding that revealed the specific marketed LA GLP‐1RA/sponsor). Communication and blinding/unblinding of these data were facilitated by the contract research organization, which also provided crucial operational oversight. Conclusions: To our knowledge, we have established the first DMC model for joint industry‐sponsored, observational, retrospective safety studies. This model could serve as a precedent for others performing similar post‐marketing, joint industry‐sponsored pharmacovigilance activities.